Pope Francis as an influential leader? How papal statements affect public attitudes toward anti-poverty measures - Ladini, Riccardo (Politics and religion, 2024)
Pope Francis has been very active in the public debate on several key social and political issues, gaining a role that foregoes the sphere of religiosity and morality. Overall, he has been perceived by the media and the general public as a leftist figure and even a modernizer. Nonetheless, little is known about the influence of Pope Francis' positions on public opinion, especially beyond the climate change issue and outside the US context. In this regard, this paper contributes to the analysis of the Francis effect on public support for poverty alleviation measures. By employing a survey experiment carried out in Italy, we therefore tested whether the papal endorsement of an anti-poverty measure during the COVID-19 pandemic affected people's support for it. The results highlighted a generalized Francis effect among the Italian public. In addition, trust in the Pope and leftist political orientation substantially enhanced this effect, while the same only partially applies to individual religiosity.